Localised low velocity impact performance of FLAX/PLA biocomposites - Nassiopoulos, Elias (Cranfield University, 2015)
Natural fibre composites are fast emerging as a viable alternative to traditional materials and synthetic composites. Their low cost, lightweight, good mechanical performance and their environmentally friendly nature makes them an ideal choice for the automotive sector. The automotive industry has already embraced these composites in production of non-structural components. At present, however, research studies into composites made of natural fibres/bio-sourced thermoplastic resins are at infancy stage and such works are rare in the literature. This study therefore focuses on the mechanical properties of poly(lactic) acid (PLA) flax reinforced composites for structural loaded components. The aim was to investigate the performance of flax/PLA biocomposites subjected to localized low velocity impacts. To start with, a detailed literature study was conducted covering biocomposites and PLA in particular. Next, a series of composite samples were manufactured. Morphological and thermal studies were also conducted in order to develop an in-depth understanding of their thermo-mechanical properties, including crystallinity, thermal response and their related transition temperatures. This was followed by localized impact studies. The influence of temperature, water uptake and strain rates to the material tensile strength and modulus, as well as the damage characteristics and limits that lead to failure were studied. Furthermore, in the present work different methods and existing material models to predict the response of biocomposites were assessed. A case study was then performed using these models to understand, develop and improve the side crash performance of a superlight city car prototype. ...[cont.]